Changes in Blood Pressure and Pulse Rate in Patients Following the Injection of Lidocaine with 2% Adrenaline in A Mandibular Nerve Block: Blood Pressure: Lidocaine with 2% Adrenaline in A Mandibular Nerve Block - Misbah, .; Hamza, Ameer; Shaikh, Muhammad Ahmed; Owais, Muhammad; Punjabi, Suneel Kumar; Hasan, Faiza; Shams, Salman; Anees, Memoona (Pakistan Journal of Health Sciences, 2025)
Local anaesthetic like lidocaine are commonly used in dental and maxillofacial procedures, but their systemic vasoconstrictive effects can cause physiological changes, especially in cardiovascular parameters. Objectives: To evaluate the blood pressure and pulse rate alterations in patients after administering a mandibular nerve block using 2% lidocaine with adrenaline. Methods: Three hundred patients aged 14-60 who came for extraction were selected through non-probability consecutive sampling. Clinical examinations were performed, and diastolic, systolic blood pressure, and pulse rate were recorded with an automatic digital blood pressure monitor in four stages (before local anesthesia (5 minutes’ rest), before local anesthesia (sitting at chair), after local anesthesia (immediate) and after local anesthesia (10 minutes)). Results: A study of 300 mandibular nerve block patients found that male patients (69.3%) and female patients (30.7%) had a mean age of 32.95 ± 11.19 years. Blood pressure, pulse rate, and oxygen saturation significantly varied in all four stages. In the first stage, most patients had normal blood pressure (120/80 mmHg), while in stages 2-4, most had stage 1 blood pressure (139/89 mmHg). In stages 3 and 4, patients had stage 2 blood pressure (140/90 mmHg), and in stage 4, 1.3% experienced hypertensive crisis. In stages 1-4, most patients had normal pulse rate, followed by tachycardia and bradycardia. Conclusions: The study found significant differences in blood pressure and pulse rate among patients after administration of a mandibular nerve block using 2% lidocaine with adrenaline.